The Role of Islamic Religious Education Teachers in Developing Interest in Reading the Qur'an in Grade V Students of State Elementary School 4 Baubau - Zuhija, Siti Chairani Femi; Rahim, Abdul; Sulasri, Sulasri (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to examine in depth the ways carried out by PAI teachers at Sekolah Elementary Negeri 4 Baubau in encouraging fifth grade students to read the Qur'an. The purpose of this research is to understand the approaches, contributions, and tactics used by PAI teachers in encouraging students to read the Qur'an regularly. A descriptive qualitative method is used. Data was collected by observing the learning process and conducting in-depth interviews with teachers and students, as well as reviewing various relevant documents and learning materials. The results show how important the role of Islamic Religious Education teachers is in encouraging students to read the Qur'an by acting as mentors, motivators, and guides. The strategies applied include the habit of reading together, giving awards or awards, and the use of creative and fun learning methods. However, this effort is still faced with obstacles such as limited time for religious lessons and the lack of parental involvement in supporting reading activities at home. Nevertheless, educators always strive to create a friendly and supportive learning atmosphere. This study shows that an ongoing interest in reading the Qur'an is largely fostered through collaboration between educators, educational institutions, and families.